Онтогенез та вікова структура популяцій сосни кедрової європейської (Pinus cembra L.) в Українських Карпатах - Sirenko, O.G. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2008)
11 stages of European cedar pine life cycle are given in the paper. Age structure from the 22 sample areas of the populations are analyzed.